Evaluating L1CAM expression in human endometrial cancer using qRT-PCR - Notaro, Sara; Altevogt, Peter (OncoTarget, 2016)
Background: Management of endometrial carcinoma (EC) still needs improvement of risk assessment. Recently, L1CAM immunohistochemical (IHC) evaluation showed a unique value to predict the outcome of early EC. However IHC results are often conflicting for lack of inter-laboratory standardisation. Methods: Here, as a proof of concept and to increase reproducibility we assayed eighty-two EC and 26 normal endometrium samples for L1CAM expression (L1CAMEXP) via qRT-PCR. The IHC evaluation was performed in 50 cancer samples. Moreover, we aimed to substantiate the in-vitro findings of L1CAM regulation through its promoter methylation (L1CAMMET), miR-34a expression and miR-34a promoter methylation. DNA methylation was assessed with MethyLight PCR technique. Results: High overall concordant results between IHC and RT-PCR evaluations were found. L1CAMEXP was detected in 11% of cancer specimens. These positive cancers exhibited a worse DFS (p=0.032) and OS (p=0.016) in a multivariate COX-regression model. L1CAMEXP predicted distant failure (p=0.007) and L1CAMMET predicted risk-reduction of lymph-node involvement (p=0.005). Inverse correlations between L1CAMEXP and L1CAMMET (p=0.004) and between L1CAMEXP and miR-34a expression (p=0.002) were found. Conclusions: In conclusion qRT-PCR analysis is a reliable approach to evaluate L1CAM status in EC and L1CAMEXP was highly predictive for distant failure and poor outcome, confirming the large IHC-based studies. Interestingly, L1CAMMET was able to assess the risk of pelvic lymph-node involvement. Especially the latter finding has to be confirmed in larger prospective series.
Gesehen am 25.06.2019